Insight into the Sulforaphane Content and Glucosinolate Profile of Broccoli Stems After Heat Treatment - Yu-Hong Zhang; Xue-Yi Liao; Zheng-Hong Li; Yu-Feng Guo; Ming-Xin Ma; Guo-Qiang Zhang (Horticulturae)
(1) Background: At the time of harvest, the stems of broccoli are frequently discarded. (2) Methods: In this study, the sulforaphane content and glucosinolate profile of broccoli stems were analyzed at different temperature treatments. (3) Results: Thermal treatment of broccoli stems for 1 h resulted in maximal sulforaphane content at 50 °C, with a subsequent progressive reduction in concentration correlating to elevated temperatures. Metabolomic analysis was conducted on broccoli stem samples subjected to 25 °C (CK), 50 °C, and 80 °C treatments. Among the 25 identified GSLs, the 50 °C-treated samples demonstrated significantly reduced GSL accumulation, whereas the 80 °C group exhibited maximal GSL retention. Indole derivatives predominated among the three GSL subclasses (aliphatic, aromatic, and indole), accounting for approximately 70% of total GSLs across all groups. The observed GSL depletion at 50 °C correlated with enhanced sulforaphane biosynthesis. Comparative analysis further indicated that 80 °C treatment induced a more pronounced elevation of indole GSLs compared to aliphatic and aromatic counterparts in broccoli stems. (4) Conclusions: The results demonstrated that indole GSLs in broccoli stems exhibit superior thermal stability. Moderate thermal treatments effectively enhance sulforaphane content, whereas exposure to 80 °C significantly increases total GSL content.